2014
DOI: 10.1364/oe.22.022730
|View full text |Cite
|
Sign up to set email alerts
|

Non-instantaneous optical nonlinearity of an a-Si:H nanowire waveguide

Abstract: We use pump-probe spectroscopy and continuous wave cross-phase and cross-amplitude modulation measurements to study the optical nonlinearity of a hydrogenated amorphous silicon (a-Si:H) nanowire waveguide, and we compare the results to those of a crystalline silicon waveguide of similar dimensions. The a-Si:H nanowire shows essentially zero instantaneous two-photon absorption, but it displays a strong, long-lived non-instantaneous nonlinearity that is both absorptive and refractive. Power scaling measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
(76 reference statements)
0
11
0
Order By: Relevance
“…The higher nonlinear refractive index arises from a free carrier effect excited by two step absorption in the existence of defect states in amorphous-Si 23 . The nonlinear refractive index has the same sign as the Kerr nonlinear index 24 . We postulate that the same phenomenon could explain the high nonlinear refractive index in USRN films.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The higher nonlinear refractive index arises from a free carrier effect excited by two step absorption in the existence of defect states in amorphous-Si 23 . The nonlinear refractive index has the same sign as the Kerr nonlinear index 24 . We postulate that the same phenomenon could explain the high nonlinear refractive index in USRN films.…”
Section: Resultsmentioning
confidence: 98%
“…It is noted that the measured nonlinear refractive index of the USRN film is higher than that in crystalline silicon. Some groups have reported that deposited amorphous Si:H has a higher nonlinear refractive than crystalline Si 23,24 . The higher nonlinear refractive index arises from a free carrier effect excited by two step absorption in the existence of defect states in amorphous-Si 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the nonlinear refractive response of both SiNSs, in some other studies it has been reported that amorphous Si–H possesses a larger nonlinear refractive index parameter γ ′ than crystalline Si [ 61 , 62 ]. The larger value of γ ′ was ascribed to free carrier refraction, induced by two-step absorption due to the presence of defects states in amorphous Si–H [ 62 ]. In addition, it was shown that the nonlinear refractive parameter γ ′ has the same sign as the Kerr effect, causing a refractive nonlinear response [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…These groups have shown a multitude of demonstrations of all-optical signal processing experiments in a-Si:H waveguides [36] and even as a source for photon pair generation [46,47]. Lastly, by investigating the time-dependent response of hydrogenated amorphous silicon waveguides, it has been observed that the Kerr-like response is far from instantaneous [48].…”
Section: Hydrogenated Amorphous Siliconmentioning
confidence: 99%